Penerapan Jaringan Syaraf Tiruan Untuk Perlindungan Transmisi Tenaga Listrik - Al Imam Akbar; Azriyenni Azriyenni (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Electricity is a very important commodity for the sustainability of the economy. The increasing demand has pushed power companies to be more efficient in the operation of the power system. Thus, the problem on reducing of the outage duration in the power system needs to be increased. Disturbance in the electric power transmission system is a critical point because it can affect a large area and can extinguish many places. In this study, the method for detecting parts are disturbed by uncertainty in the transmission system, then, the theories of Artificial Neural Networks (ANN) is used. This ANN method aims to apply an artificial intelligence system to estimate the performance of protective equipment in the electric power system. Training and testing data are is generated by simulating single-phase to ground faults with variations in each channel. The operating time of the protection equipment will result in the Circuit Breaker (CB) status when operates. The transmission system that the object of research are 5 buses power system (system interconnection Riau) which is modeled via Matlab/Simulink, then used to run 5 fault scenarios to obtain changes in relay and CB status. The simulation result data is then used to test the ANN model. The simulation results obtained are the fault current output of each transmission line.Keywords: ANN, Transmission Line, Fault Current, Relay, Circuit Breaker